ACHIEVING OF INCOME TAX WITH AWARENESS OF TAXATION IN INDONESIA'S TAX LAW SYSTEM - Anggia, Putri (Faculty of Law, Universitas Sebelas Maret, 2019)
The journey of Indonesian taxation is full of dynamics in order to get the State's revenue target as the main source of the country's economy. Furthermore fulfillment of the country's income depends on ongoing policies. However Indonesian people does not found a point that the obligation to pay taxes is a form of voluntary awareness as citizens. This was captured by the Government as one of the points that must be observed and acted upon. The Minister of Finance Decree Number 36 / KMK.01 / 2014 concerning the Blueprint of the Ministry of Finance's Transformation Program for 2014-2025 provides space to take several steps in an effort to increase understanding of tax awareness through education. This study aims to examine in depth about tax education in the tax law system in Indonesia. The methodology used in this study is literature study that the data collection techniques, and library research aim to examine primary legal materials, secondary legal materials, and tertiary legal materials. The library materials are summarized and analyzed. This research found an assertive concept that was applied massively, consistently, and could be accepted by every society in order to succeed the goal of achieving tax awareness. It is tax compliance.